Redução fotocatalítica de Hg(II) a Hg0 em diferentes sistemas reacionais - Coelho, Ana Letícia Silva (2016)
Heavy metals are usually non-degradable, exhibiting long half-life, raising thus its concentration in food chains to toxic levels.. The mercury in concentration above 0,005 ppm is considered toxic, therefore is included in the list of priority pollutants the US EPA, with maximum exposure of 200 ppb. The titanium dioxide and zinc oxide are semiconductors fairly applied in photocatalysis reactions, because its chemical and thermal stability, high photoactivity, low cost and non-toxicity. However these materials are semiconductors with high energy band gap (EZnO = 3,37 eV; Eanatase = 3,20 eV ), this requires wavelength below 400 nm for excitation thereof. Thus, it is essential to promote the activity of semiconductors for visible light region . In order to reduce recombination of electron/hole pairs, it is possible to modify the surface of ZnO and TiO2 by doping with transition metals. Iron has been considered an appropriate candidate to doping, owing to the radius of Fe3+ (0.64 Å) being similar to that of Ti4+ (0.68 Å) and Zn2+ (0,83 Å). Thus, doped with different iron concentration (5%, 8%, 10% e 15% wt) TiO2 and ZnO photocatalyst were synthesized by the impregnation method. The photocatalytic reduction of Hg2+ to Hg0 was performed in batch stirred tank reactor (BSTR) and solar reactor, under four different conditions reactions (Ci): (C1) aqueous HgCl2 120 ppm; (C2) aqueous HgCl2 120 ppm and formic acid at a concentration of 10 mM; (C3) aqueous HgCl2 120 ppm oxygen, dispersed in the reaction medium; (C4) aqueous HgCl2 120 ppm formic acid at a concentration of 10 mM and oxygen and dispersed in the reaction medium. Characterization of doped and bare materials was performed by TGA / DSC, BET area, pore diameter and pore volume, PZC, EDX, SEM, DRX, FT-IR, spectroscopy photoacoustic and spectroscopy Mossbauer. The photocatalytic reduction of Hg2+ to Hg0 was performed in batch stirred tank reactor (BSTR), in the presence of catalysts, under four different conditions reactions. The results showed that the bare ZnO completely reduce Hg (II) in all investigated conditions and reaction systems. However, the addition of iron in the ZnO (ZnO / Fe) decreased pollutant reduction efficiency in batch reactor, showing no reduction ability of Hg (II) in the presence of sunlight. The data show that addition of iron modify the electronic structure of TiO2 by the incorporation of Fe3+ in matrix of semiconductor, although only 8 wt% showed improving the photo-activity in reduction, with a total Hg2+ removal ratio for Hg0 in BSTR, no reduction ability of Hg (II) was observed in the presence of sunlight. The bare commercial TiO2 and those containing 5, 10 and 15 (wt%) of iron were not efficient in the reduction of Hg at any experimental condition and reaction system studied.